Diabetes and Brain Health - DOLAN, CATHERINE MARGARET (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
Introduction: Type 2 diabetes mellitus (T2DM), one of the most common non-communicable diseases in the world, is linked to multi-organ complications. Such complications include cognitive impairment, dementia and depression. These brain health complications have an adverse impact on diabetes outcomes. Given the projected increase in prevalence globally of T2DM and dementia, identifying effective prevention strategies for both, in tandem with timely effective management of brain health complications of diabetes, is an important target. As a first step, this study aimed to establish levels of awareness of the effects of diabetes on brain health among individuals with diabetes and the general public. Method: A narrative review of the literature found no validated survey instrument available to assess diabetes and brain health awareness. For this reason, a systematic review of the literature and a Delphi study were used to develop consensus on (i) potential brain-related complications of diabetes and, (ii) the common modifiable risk factors for T2DM and dementia. Information from this literature review and results of the Delphi study informed the design of the survey measure used in the Diabetes and Brain Health (DBH) study. Following the development of the DBH questionnaire, it was administered by an interviewer to a sample of individuals with diabetes and members of the general population in Ireland, in a cross-sectional study. Results: Thirteen studies out of 9,709 abstracts that were identified in the systematic review, were included in a qualitative synthesis of results. As this review identified mainly observational evidence linking diabetes and brain health, a Delphi study was undertaken as a next step in establishing DBH questionnaire content validity. Of 46 international experts invited to take part in the Delphi study, there was a response rate of 32%. The expert panel reached agreement on memory problems, dementia and depression as brain health complications of diabetes. The panel also reached consensus on the following risk factors for T2DM, also recognised as dementia risk factors: hypertension, obesity, physical inactivity and heavy alcohol consumption. A consensus was not reached on depression, cognitive inactivity, smoking and high cholesterol as T2DM risk factors. In the cross-sectional study, there were 502 adult respondents to the subsequently developed DBH questionnaire; 250 in diabetes group (37% women, mean age 63 +/-14 years) and 252 in general population (51% women, mean age 47 +/-17 years). Among the total group, levels of awareness of memory problems (47%), dementia (35%) and depression (63%) as potential complications of diabetes were low, compared to respondent awareness of kidney (84%) and eye damage (84%). Respondents were 1.5 times more likely to identify that individuals can modify their risk of developing T2DM, compared to being able to modify their risk of developing dementia. Except for depression, the diabetes group attending St James?s Hospital, had significantly higher awareness levels of diabetes complications, including memory problems and dementia, compared to the general population group. Conclusion: These results point to a low level of awareness of the effects of diabetes on brain health among individuals with diabetes and the general population in Ireland. They would suggest a need to expand diabetes education programmes to promote awareness of the link between diabetes and brain health. Public awareness campaigns relating to dementia prevention need to emphasize the role of modifiable risk factors, including T2DM, physical inactivity and obesity, as part of a life-course approach to dementia prevention.
APPROVED
Keywords: Type 2 Diabetes Mellitus; Brain Health; Dementia; Depression; Diabetes complications